THE EFFECT OF SPECIAL EXERCISES USING LOWPOWER LASER IN REHABILITATING REFLEX ANKLE SPRAIN INJURIES IN ADVANCED BASKETBALL PLAYERS - Assistant Lecturer Rana Qais Sultan; MBChB. Msc. Ph.D Zeyad Tareq Abdulrazzaq (Proximus Journal Publishing, 2024)
The research aims to prepare special exercises using a low-power laser to rehabilitate a reflex ankle sprain injury for advanced basketball players, and to identify the effect of exercises using a low-power laser to rehabilitate a reflex ankle sprain injury for advanced basketball players. To achieve the goal, the researcher used the experimental method with pre-test and post-test to suit it with the research problem. The research sample was chosen intentionally from advanced basketball players with reflex ankle sprain for Baghdad clubs for the sports season (2023/2024), numbering (12) players representing the original research community. 100%, after diagnosing the injury, its severity, and medical history from the specialist doctor. The researcher also chose players as a reconnaissance sample and they were excluded from the main sample, The researcher conducted a pre- and post-test for the members of the research sample, and conducted appropriate statistical treatments. The researcher concluded that there was a clear development for the members of the research sample in the variables investigated when using laser rehabilitation exercises with special exercises, and that using the laser approach with special exercises helped better in the rehabilitation process. Relieves reflex sprain injury to the ankle joint by improving the range of motion and muscle strength of the joint
Keywords: Low laser power; ankle sprain